Lagos Mainland Residents’ Perception of Media Reportage on Electricity Tarief Hike in Lagos State, Nigeria - Fatimat, Ogunyemi Oluwafisayo; Dorcas, Fadeyi Oluwadamilola; Nwaoboli, Emeke Precious (Pancasila International Journal of Applied Social Science, 2025)
The researchers examined Lagos mainland residents’ perception of media reportage on electricity tariff hike. The objectives of the study were to examine the extent of awareness of Lagos mainland residents of media reportage on electricity tariff hikes; determine the media channel through which the Lagos mainland residents access reports on electricity tariff hikes; investigate the perceived credibility of media reports on electricity tariff hikes among Lagos mainland residents and to explore the relationship between media reportage and public perception of electricity tariff hikes among Lagos mainland residents. The researchers adopted the survey research design, while the questionnaire was used as the instrument for data collection. Findings revealed that the majority of the respondents had a high 164 (43.7%) level of awareness of media reports on electricity tariff and that the majority 169 (45.1%) access the media reportage of the increase through social media and the internet 98 (26.1%). Consequently, the media’s reportage has yielded positive outcomes, including heightened awareness and public discourse on the economic and social implications of the tariff increase, thereby amplifying their voices and advocating for their interests. Ultimately, the researchers recommended that the media should continue to critically report on the electricity tariff hikes, highlighting the impact on the public. It was also recommended that policymakers in Lagos State review the electricity tariff hikes to ensure they are fair and reasonable and take into account the economic and social implications for the public.